2001
DOI: 10.1080/01926230152500086
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Background Lesions and Tissue Accountability for Male Accessory Sex Organs in Fischer-344 Rats

Abstract: Because the paired lobes (ventral, dorsal, lateral, and anterior) of the rat prostate have not been consistently sampled in many carcinogenicity and toxicity studies, comparison among different investigations has been compromised. The lack of specific site identification for prostatic lesions further lessens the value of incidences reported. We present here the lobe-specific incidences and degree of severity of background prostatic, seminal vesicular, and ampullary glandular lesions in 1768 control Fischer-344… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
3
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 39 publications
5
44
3
1
Order By: Relevance
“…The change is also sometimes associated with chronic inflammation of the vesicle wall and may be secondary to ascending urinary tract infections, which are relatively common in male mice. Mucinous cystic acini (cysts) have also been described in the prostate of aging rats and mice (Suwa et al 2001(Suwa et al , 2002. Similarly, dilation of the bulbourethral glandular acini or ducts, progressing to cystic atrophy may be observed in aging rats and mice where enlarged bulbourethral glands are often sampled as gross abnormalities (Kiupel, Brown, and Sundberg 2000;Wardrip et al 1998).…”
Section: Bulbourethral Glandmentioning
confidence: 99%
See 3 more Smart Citations
“…The change is also sometimes associated with chronic inflammation of the vesicle wall and may be secondary to ascending urinary tract infections, which are relatively common in male mice. Mucinous cystic acini (cysts) have also been described in the prostate of aging rats and mice (Suwa et al 2001(Suwa et al , 2002. Similarly, dilation of the bulbourethral glandular acini or ducts, progressing to cystic atrophy may be observed in aging rats and mice where enlarged bulbourethral glands are often sampled as gross abnormalities (Kiupel, Brown, and Sundberg 2000;Wardrip et al 1998).…”
Section: Bulbourethral Glandmentioning
confidence: 99%
“…The mucosa has a honeycombed structure formed by complex folding to produce irregular anastomosing channels that communicate with the central cavity; thin primary folds of the mucosa also extend out into the vesicle lumen. The epithelium is composed of pseudostratified columnar cells in the mouse and simple columnar epithelium in the rat (Suwa et al 2001(Suwa et al , 2002. The secretory material from this gland is intensely eosinophilic and constitutes 50 to 80% of the ejaculate (Creasy and Foster 2002).…”
Section: Seminal Vesiclementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been found that there is a significant association between spontaneous inflammation in the dorsolateral lobes of prostate and prolactin positive pituitary gland adenomas in Fisher-344 rats; this finding supports the hypothesis that prolactin plays an important role in the pathogenesis of prostatic inflammation. 141 It has been also shown that prepubertal (postnatal days 22-32) exposure to various compounds that increase prolactin secretion, including pimozide (a dopamine antagonist), bisphenol A (a monomer of polycarbonate plastic reported to have weak estrogenic activity), and 17b-estradiol, albeit through different mechanisms, can increase the incidence of inflammation in the lateral prostate the Wistar rats. 142,143 Shyr et al 144 used daily injections of bromocryptine to depress maternal plasma and milk PRL levels in lactating rats.…”
Section: Rat Models Of Prostatitismentioning
confidence: 99%